UTILIZATION OF ‘TALI AIR’ BATIK STAMP IN EMPOWERING CREATIVE RESOURCE IN BANDUNG - Ghaida Nasya Putri; Yan Yan Surnarya; Achmad Haldani Destiarmand (Fakultas Seni Rupa dan Desain ITB, 2018)
'Tali air' batik stamp is a tool to create batik which is a single perpendicular line stamp by using hot wax. 'Tali air' batik stamp has a great potential to create various main ornaments but this technique has not been utilized yet for designing fashion products from Bandung. In this study ‘tali air’ batik stamp is utilized in empowering creative resource in Bandung. Method used in the study is qualitative method that is exploration by observing and discussing as data collection techniques. The result of empowering in this study is a prototype of 'Tali air' batik stamp product. This study can be developed to utilize 'Tali air' batik stamp in empowering non creative society or creative resource from areas other than Bandung.